Income inequalities and mortality by generation among individuals with a foreign background in Sweden: a population-based studyResearch in context - Alexander Miething; Andrea Dunlavy; Sol P. Juárez (The Lancet Regional Health. Europe)
Summary: Background: Evidence shows that both the mortality advantage and the lower income inequalities in mortality that characterise recent international migrants tend to disappear with time spent in the receiving country. This study examines whether absolute and relative income inequalities in mortality also increase by migrant generation in Sweden. Methods: Longitudinal data from Sweden’s population registries (2004–2018) was used to identify residents aged 25–64. An open cohort design was employed using slope (SII) and relative (RII) indices of inequality from negative binomial regressions to estimate associations between income rank position and all-cause mortality among majority population Swedes and individuals with a foreign background, classified by generation and by European or non-European origin. Sub-analyses assessed the contribution of external causes to income inequalities in mortality. Findings: Male descendants of migrants with non-European backgrounds exhibited higher relative income inequalities in mortality (ranging from RIIG2.5: 6.72 to RIIG2: 11.47) than first generation non-European migrant (RII: 1.7; 95% confidence interval (CI): 1.28–2.26) and majority population men (RII: 4.73; 95% CI: 4.36–5.12). External causes accounted for 56–60% of these inequalities in mortality. Absolute income inequalities in mortality among men showed similar patterns to those observed for relative inequalities. Women showed lower absolute and relative inequalities compared to men across origins and by generation. Interpretation: Income-related inequalities in mortality appear to increase by migrant generation, particularly among men with non-European backgrounds, with external causes playing a significant role. Health and non-health targeted interventions focusing on social determinants are needed to address income inequalities in mortality. Funding: Swedish Research Council for Health, Working Life and Welfare, and Swedish Research Council.